Association of interferon-γ and interferon regulatory factor 1 polymorphisms with asthma in a family-based association study in Taiwan - Wang, T.-N.; Chu, Y.-T.; Chen, W.-Y.; Feng, W.-W.; Shih, N.-H.; Hsiang, C.-H.; Ko, Y.-C. (Clinical and experimental allergy, 2006)
Summary Background Asthma is a multi‐factorial disorder caused by complex interactions between genetic and environmental factors. IFN‐γ and IFN regulatory factor 1 (IRF‐1) affect Th1/Th2 cytokine balance, and influence the differentiation of Th2 cells, which influence the development of asthma. Objective This study investigated CA repeats polymorphism of the IFN‐γ gene and GT repeats polymorphism of the IRF‐1 gene, which may predispose individuals to asthma pathogenesis. Methods In the present study, we used the transmission/disequilibrium test (TDT) to investigate the relationship between asthma and the IFN‐γ and IRF‐1 polymorphisms by studying 348 subjects composed of 232 parents and 116 asthmatic children. Results For global TDT test, IFN‐γ CA repeats and IRF‐1 GT repeat polymorphisms showed a significant association with asthma in children (P=0.009 and 0.017, respectively). We demonstrated that 13 CA repeats (138 bp) of IFN‐γ gene and 11 GT repeats (306 bp) of IRF‐1 gene are significantly preferentially transmitted to asthmatic children (T/NT=89/61, χ2=8.43, P<0.005 and T/NT=75/49, χ2=8.18, P<0.005, respectively). The offspring will have an increased risk of asthma when their parents transmit IFN‐γ 13 CA repeats (OR=1.83, P=0.009) and IRF1 11 GT repeats (OR=1.88, P=0.007) to them. But we observed that the IFN‐γ and IRF‐1 polymorphisms are not associated with IgE concentrations. Conclusion These findings provide strong evidence of which IFN‐γ CA repeat and IRF‐1 GT repeat polymorphisms influence the risk of asthma for children in Taiwan.